1982
DOI: 10.1258/002367782780891660
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis in rhesus monkeys

Abstract: 9 Cases of endometriosis in rhesus monkeys were found in a colony of 35 females, which had undergone in the past X-ray treatment or one or more Caesarean sections and/or one or more treatments with gonadal steroids. Incidence, pathogenesis, clinical symptoms, histology and treatment are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…The tortuous blood vessels in the gastrocolic omentum resembled the spiral arteries in the human and simian endometrium 2 . The morphological structures in the present case were similar to those of reported endometriosis in rhesus monkeys [3][4][5] , and this case was, therefore, diagnosed as endometriosis.…”
supporting
confidence: 87%
“…The tortuous blood vessels in the gastrocolic omentum resembled the spiral arteries in the human and simian endometrium 2 . The morphological structures in the present case were similar to those of reported endometriosis in rhesus monkeys [3][4][5] , and this case was, therefore, diagnosed as endometriosis.…”
supporting
confidence: 87%
“…Such would be the case if the risk of a fecundity loss increases with each additional year of life or the cumulative 'wear and tear' associated with repeated parturitions. In fact, previous research has already shown that both age (van Wegenen, 1972;Hodgen et al, 1977;Graham et al, 1979) and parity (McCann and Myers, 1970;Bertens et al, 1982) are associated with a deterioration of the reproductive capacity of female macaques.…”
Section: Discussionmentioning
confidence: 95%
“…Except for a few spontaneous endometriosis [8], most cases in rhesus monkeys have been thought to be the sequela of hysterotomy or chronic effects of irradiation [1,3,6,7,[9][10][11][12]. Present two cases, however, were free from these treatment at least for 9years as far as we are concerned.…”
mentioning
confidence: 87%
“…Endometriosis is not uncommon in rhesus monkeys, and it has been reported as a sequela to hysterotomy with additional effects of ovarian steroids [1,3,4,6,9,10] and as a latent effect of irradiation [1,6,7,9,11,12] . In most of the reported cases in rhesus monkeys, the lesion was limited to the wall of pelvic organs [1,3,[6][7][8][9][10]12] . The severe cases presented in this report are of particular interest due to widespread disseminationn of the endometrial tissues without prier histories of uterotomy nor irradiation.…”
mentioning
confidence: 99%